2000
DOI: 10.5914/tropocean.v28i1.2743
|View full text |Cite
|
Sign up to set email alerts
|

Camarões de Profundidade coletados no norte do Brasil (Crustacea: Penaeidea e Caridea).

Abstract: A realização de prospecções entre as isóbatas de 300 e 600 metros, na Região Norte brasileira, entre os Estados do Amapá e Maranhão, a partir da implantação do Programa “REVIZEE”, propiciou a obtenção de um excelente acervo zoológico. Entre estes, ressaltam-se os crustáceos, representados, primordialmente, pelos Penaeidea e Caridea. As coletas foram realizadas durante o segundo semestre de 1996 e primeiro de 1997 e 1998, a bordo do Navio de Pesquisa “Almirante Paulo Moreira”, sob a responsabilidade do Centro d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 3 publications
1
13
0
1
Order By: Relevance
“…Lemaitre (1984) recorded the species in the Bahamas, between depths of 446-453 m, whilst Holthuis (1971) recorded the species between 256-692 m, similar to the depths reported by Pequegnat (1970) and Ramos-Porto et al (2000). In the present study, the species was found between the depths of 389-480 m.…”
Section: Glyphocrangon Spinicauda a Milne-edwards 1881supporting
confidence: 74%
See 4 more Smart Citations
“…Lemaitre (1984) recorded the species in the Bahamas, between depths of 446-453 m, whilst Holthuis (1971) recorded the species between 256-692 m, similar to the depths reported by Pequegnat (1970) and Ramos-Porto et al (2000). In the present study, the species was found between the depths of 389-480 m.…”
Section: Glyphocrangon Spinicauda a Milne-edwards 1881supporting
confidence: 74%
“…Komai (2004a: 41) assumed the first record of this species from Brazilian waters based on material collected by the project REVIZEE Score Central off Bahia coast. This author pointed out that G. spinicauda has been cited on an unpublished conference abstract record by Ramos-Porto & Silva (2000). However, Komai (2004a) probably overlooked that Holthuis (1971) had already recorded this species in Brazil on the basis of eight ovigerous females collected at station of "Oregon" St. 2081 off the outfall of the Amazon River in the state of Pará.…”
Section: Glyphocrangon Spinicauda a Milne-edwards 1881mentioning
confidence: 99%
See 3 more Smart Citations